1991
DOI: 10.2519/jospt.1991.14.6.263
|View full text |Cite
|
Sign up to set email alerts
|

Intraexaminer, Interexaminer, and Interdevice Comparability of Leg Length Measurements Obtained with Measuring Tape and Metrecom

Abstract: nequalities in leg length, whether anatomical o r cre-21 ated by artificial means (such J as lifts), are known to have i i some specific effects on the posture of standing individuals. Among the effects of leg length discrepancies are lateral pelvic tilts (1, 2, 8). scoliotic curves (2, 3), and alterations in weight bearing patterns (8). Potentially more important than these effects, however, is the possible association between leg length discrepancies and low back pain. Although all studies of the issue have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
8

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 4 publications
1
15
0
8
Order By: Relevance
“…Hoyle et al 32 reported intraclass correlation coefficients (ICCs) between repeated tape measurements from the anterior superior iliac spine to the medial malleolus that were similar to those reported by Friberg et al 18 The ICC 3,1 for 25 subjects between 2 examiners for the left limb was 0.99 with a range of differences between examiners of 5.0 to 23.0 mm. The ICC 3,1 for 25 subjects between 2 examiners for the right limb was 0.98 with a range of differences of 0.0 to 28.5 mm.…”
Section: Clinical Assessmentsupporting
confidence: 58%
See 1 more Smart Citation
“…Hoyle et al 32 reported intraclass correlation coefficients (ICCs) between repeated tape measurements from the anterior superior iliac spine to the medial malleolus that were similar to those reported by Friberg et al 18 The ICC 3,1 for 25 subjects between 2 examiners for the left limb was 0.99 with a range of differences between examiners of 5.0 to 23.0 mm. The ICC 3,1 for 25 subjects between 2 examiners for the right limb was 0.98 with a range of differences of 0.0 to 28.5 mm.…”
Section: Clinical Assessmentsupporting
confidence: 58%
“…The authors concluded, therefore, that tape measurements by different clinicians should not be compared. The study by Hoyle et al 32 did have 2 major methodological problems. Subjects were measured repeatedly with an insufficient interval between measurements to prevent rater bias, and it is not clear if examiners were masked to each other's results.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Studies have demonstrated that the Metrecom was reliable when used for assessments of inanimate objects (17) and human leg length measurements (9). In a recent study, Smidt et al (20) evaluated the Metrecom for accuracy, repeatability and linearity, and for human skeletal landmark location reliability.…”
Section: Instrumentationmentioning
confidence: 99%
“…Además, Gogia y Braatz publicaron un trabajo en relación con las radiografías (ICC= 0.98) y una fiabilidad inter e intraexaminador de (ICC=0.98) (26). Hoyle y sus colaboradores, observaron una fiabilidad interexaminador de r=0.98 y una fiabilidad intraexaminador que iba desde r=0.89 a r=0.95 para la medición desde la EIAS al maléolo tibial (27) Woerman y Binder-MacLeod compararon el método indirecto y ambas variantes del método directo con las radiografías, y concluyeron que el método indirecto era más exacto y preciso que cualquiera de los métodos directos (11). Los autores abogaron por el uso del método indirecto, especialmente en caso de que pudiera tratarse de una disimetría funcional de la longitud de las piernas.…”
Section: Discussionunclassified